Critical evaluation of overall business operation of Paxar Bangladesh Ltd : A subsidiary of Avery Dennison Corporation - Mallick, Animash (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2015.